The Implementation of Balanced Literacy Approach To Early Childhood Education Units As An Effort To Strengthen Learning: A Phenomenological Study After The Covid-19 Pandemic In Indonesia - Farida K., Anna; Tutty R Rosa, Ade; Andriana Gaffar, Muhammad; Cahyani, Rianti (International Journal of Educational Research & Social Sciences, 2022)
Research by Indonesian Ministry of Education, Culture, Research, Technology in 2020-2021 found a significant decrease of learning outcomes in the first grade of elementary school students as a result of the Covid-19 pandemic. The Early Childhood Education as the foundation phase plays a crucial role in the learning recovery, especially literacy. This study explores and analyzes the experiences of Early Childhood Education (PAUD) teachers in applying balanced literacy approach as an effort to strengthen learning. This research refers to the literary processing theory by Clay (Ronning, 2020: 17) regarding the acquisition of literacy skills in early childhood. The method used is qualitative phenomenology with 10 teachers from several regions of Indonesia as informants. The analysis was about the experience of teachers applying balanced literacy before and during the pandemic, the obstacles faced, and the solutions carried out. These findings become the basis for designing the product of this study, namely a conceptual model of early literacy strengthening program with balanced literacy in PAUD. This model is expected to be a contextual alternative solution for strengthening effective literacy in the post-pandemic period and minimizing the impact of learning loss in Indonesia.